Temporal Sequence of Cell Wall Disassembly in Rapidly Ripening Melon Fruit - Rose, Jocelyn K.C. (American Society of Plant Physiologists, 1998)
The Charentais variety of melon (Cucumis melo cv Reticulatus F1 Alpha) was observed to undergo very rapid ripening, with the transition from the preripe to overripe stage occurring within 24 to 48 h. During this time, the flesh first softened and then exhibited substantial disintegration, suggesting that Charentais may represent a useful model system to examine the temporal sequence of changes in cell wall composition that typically take place in softening fruit. The total amount of pectin in the cell wall showed little reduction during ripening but its solubility changed substantially. Initial changes in pectin solubility coincided with a loss of galactose from tightly bound pectins, but preceded the expression of polygalacturonase (PG) mRNAs, suggesting early, PG-independent modification of pectin structure. Depolymerization of polyuronides occurred predominantly in the later ripening stages, and after the appearance of PG mRNAs, suggesting the existence of PG-dependent pectin degradation in later stages. Depolymerization of hemicelluloses was observed throughout ripening, and degradation of a tightly bound xyloglucan fraction was detected at the early onset of softening. Thus, metabolism of xyloglucan that may be closely associated with cellulose microfibrils may contribute to the initial stages of fruit softening. A model is presented of the temporal sequence of cell wall changes during cell wall disassembly in ripening Charentais melon.